THE INFORMATIVENESS AND THE CONTENT OF MASS DOCUMENTATION OF THE GENERAL INSPECTION OF THE NOBILITY IN1721-1723 - A. V. Zakharov (Гуманитарные и юридические исследования)
The General Inspection of the Nobility was conceived by Peter the Great as a large-scale recruitment campaign for the civil service of all nobles who were not in army regiments. The Inspection was held in St. Petersburg and Moscow in 1721-1723 and ended with an audit and new appointments of about 17 thousand people to civil service and resignations. The number of people assigned to the Inspection turned out to be bigger than in the wellknown decrees. The article studies the informativeness, identification and composition of the documents of this Inspection which contained personal data. The author identified a template for writing «skazki» at the Tsar Fyodor Alekseevich’s Inspection and compared similar sources of 1681 – 1722. For the first time, the author established a relatively complete volume of «skazki», of feature «priezdy» and «doprosy». He determined the connection of «interrogations of netchiks» containing their verbal portraits with the history of the general review. Analyzing the Deployment Books of the «opredelenii», the author briefly justified the opinion about their identity to the «Lists of the military ranks». New data about the staff of the Heraldry office under Senate and the completion of the Inspection in Moscow are given. The author concludes about the active borrowing of the discharge mechanism, documentation forms in the 1720s. The Senate and the Heraldry office expanded bureaucratic administration in large-scale recruitment campaigns of the nobility and officials.